Two Birds with One Stone: Health Care Providers’ Perspectives about Prevention Technologies in Kenya and South Africa - Alexandra Lutnick PhD; Mary Kate Shapley-Quinn MPH; Kgahlisho Nozibele Manenzhe BSocSciHons; Jacob Onyango MA; Kawango Agot PhD, MPH; Khatija Ahmed MMed; Ariane van der Straten PhD, MPH (Journal of the International Association of Providers of AIDS Care, 2019)
To meet the reproductive health needs of women, especially those in sub-Saharan Africa, multipurpose prevention technologies (MPTs) that combine pregnancy and HIV prevention into a single product could be highly beneficial. This qualitative study with health care providers in Kenya and South Africa examined health system factors that may facilitate or inhibit the delivery of these MPTs. Twelve qualitative interviews were conducted with health care providers at each site (24 interviews total). Providers were presented with pictures and actual placebo prototypes of 4 MPTs: a vaginal ring, an oral pill, an injectable, and an implant. Four themes emerged related to health care providers’ reported interest in offering the proposed MPTs: (1) perceptions of young women’s interest in the MPTs, (2) considerations about product administration, (3) feedback about product attributes, and (4) providers’ training needs. Overwhelmingly, health care providers are eager to offer a product that prevents both HIV and unintended pregnancy in young women.